The Nature-Study Idea And Related Writings - Bailey, Liberty Hyde (Cornell University Press, 2024)
In The Nature-Study Idea, Liberty Hyde Bailey articulated the essence of a social movement, led by ordinary public-school teachers, that lifted education out of the classroom and placed it into firsthand contact with the natural world. The aim was simple but revolutionary: sympathy with nature to increase the joy of living and foster stewardship of the earth. With this definitive edition, John Linstrom reintroducesThe Nature-Study Idea as an environmental classic for our time. It provides historical context through a wealth of related writings, and introductory essays relate Bailey's vision to current work in education and the intersection of climate change and culture. In this period of planetary turmoil, Bailey's ambition to cultivate wonder (in adults as well as children) and lead readers back into the natural world is more important than ever.